Propriedades biológicas e químicas de solos arenoso e argiloso tratados com isolados fúngicos sob soja e milho em casa-de-vegetação - Barbosa, Bruno Borges (2021)
With the increase of the growing population, the urge to develop the food production in order to ensure sustainability and environmental conservation intensified. Many practices of conventional agricultural management have impacted negatively physical, chemical and biochemical properties of the soil, leading to losses on functionality and environmental quality. In this way, it becomes important to develop practices that contribute to the systems sustainability, reducing observed impacts on agricultural land use, such as beneficial microorganisms. Plant growth promoting fungi (PGPF) can improve plants' health, pest control, and have a potential effect on soil variables. In this context, this study aims to identify the effects of five isolated fungi (Beauveria bassiana, Trichoderma asperellum, Metarhizium anisopliae, Purpureocillum lilacinum, Pochonia chlamydosporia) conditioning chemical and biological variables of clayey and sandy soil under soybean and corn plantation. Therefore, an experiment was performed with corn and soybeans on clayey and sandy soils in a vegetation house. Each sample received 6 treatments of fungal isolated application, totaling 4 attempts for each treatment. Thus, the following treatments were applied in each experiment: 1 – Uninoculated control; 2 – Beauveria bassiana; 3 – Metarhizium anisopliae; 4 – Pochonia chlamydosporia; 5 –Purpureocillium lilacinum; and 6 – Trichoderma asperellum. The arbuscular mycorrhizal colonization, soil fertility, enzyme activity, microbial basal respiration, carbon from soil biomass and plant dry mass were analyzed. The experiments were fully randomised. Portions of the applied isolated fungi influenced the fertility of the soil, in parameters such as pH, potential acidity, magnesium, and base saturation. The application of any fungi conditioned greater colonization of roots by arbuscular mycorrhizal fungi, ranging from: 48.6% to 56.2% for inoculated treatments and 32.5% for the application in the corn test on sandy soil; from 59.5% to 66.8% for inoculated treatments and 46.3% in the experiment of corn on clayey soil; from 47.2% to 58.3% for inoculated treatments and 29.9% for the application in the soybean test on sandy soil; from 60.8% to 68.9% for inoculated treatments and 33.6% for the application in the soybean test on clayey soil. The parameters of soil fertility and enzymatic activity, presented changes in variables in certain treatments, being inconsistent in the two soils and two crops, but indicating specific soil-plant-microorganism interaction effects. The plant growth, microbial basal respiration and microbial biomass carbon were not influenced by the isolated fungi.